Integration, Concentration, and Profits in Manufacturing Industries - Fuchs, Victor R. (Quarterly Journal of Economics, 1961)
Introduction, 278. — I. Comparisons of sizes and operating characteristics within industries among different types of establishments, 279. — II. Inter-industry differentials in multi-unit operations; multi-unit operations and other industry characteristics, 283.